HUBUNGAN KARAKTERISTIK PERAWAT DENGAN RESTRAIN PASIEN GADUH GELISAH DI INSTALASI GAWAT DARURAT RUMAH SAKIT ERNALDI BAHAR PROVINSI SUMATERA SELATAN - Riko, Riko Sandra Putra; Diana H.Soebyakto; Henda, Elma; Ari Wiryansyah, Oscar (LPPM STIKes Mitra Adiguna, 2023)
There are many challenges that must be faced by nurses when they have to deal with agitated patients with restraint, because at any time the patient can act aggressively and endanger the environment. The purpose of this study was to determine the relationship between age, educational level and years of service of nurses with the restraint of anxious and agitated patients. The design of this research is quantitative using cross sectional analytic survey method. The sample of this study were all nurses working in the emergency room at Ernaldi Bahar Hospital as many as 30 people. Data analysis in this study was carried out using univariate and bivariate methods. It was found that there was a relationship between the age of the nurse and the restraint of the patient from being anxious, with p value = 0.028; there is a relationship between nurse's education and restraint of anxious patients, with p value = 0.015; there is a relationship between the length of service of nurses and the restraint of anxious patients, with p value = 0.023. Conclusion based on the results of the study it can be concluded that there is a relationship between the age of the nurse, education, and the period of service of the nurse with the restraint of the patient being anxious